2014
DOI: 10.1007/s11096-014-9954-5
|View full text |Cite
|
Sign up to set email alerts
|

The Utrecht Pharmacy Practice network for Education and Research: a network of community and hospital pharmacies in the Netherlands

Abstract: Practice-based networks can serve as effective mechanisms for the development of the profession of pharmacists, on the one hand by supporting student internships and on the other hand by collection of research data and implementation of research outcomes among public health practice settings. This paper presents the characteristics and benefits of the Utrecht Pharmacy Practice network for Education and Research, a practice based research network affiliated with the Department of Pharmaceutical Sciences of Utre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
61
0
1

Year Published

2015
2015
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 58 publications
(65 citation statements)
references
References 18 publications
0
61
0
1
Order By: Relevance
“…has been re-professionalized with patient-centered care as its focus (Bond, 2006;Hassali et al, 2011;Koster et al, 2014). As a result of the paradigm shift within the profession, pharmacists are now more involved in direct patient care (Academic Medical Centers, 2010).…”
Section: Author(s) Agree That This Article Remain Permanently Open Acmentioning
confidence: 99%
See 2 more Smart Citations
“…has been re-professionalized with patient-centered care as its focus (Bond, 2006;Hassali et al, 2011;Koster et al, 2014). As a result of the paradigm shift within the profession, pharmacists are now more involved in direct patient care (Academic Medical Centers, 2010).…”
Section: Author(s) Agree That This Article Remain Permanently Open Acmentioning
confidence: 99%
“…As a result of the paradigm shift within the profession, pharmacists are now more involved in direct patient care (Academic Medical Centers, 2010). According to the literature, this shift to the social context requires rethinking the process of professional training (De Oliveira, 2011;Koster et al, 2014). Ivama (1999) and Nicoleti (2010) observed that pharmaceutical education must follow social and political trends.…”
Section: Author(s) Agree That This Article Remain Permanently Open Acmentioning
confidence: 99%
See 1 more Smart Citation
“…However, we only included a small sample of pharmacies in the Netherlands (*2 %) and within these pharmacies a small sample of users of a selection of drugs, thus on a population-based level there might be a considerable proportion of preventable medication errors due to unavailability of laboratory values. The included pharmacies are a good representation of Dutch pharmacies in general [7] and all pharmacies providing internships during the study period participated, thus selection bias seems unlikely. We focused on use of a single eGFR cut-off value of \45 ml/min and \13 months old, when using more strict criteria, e.g.…”
Section: Discussionmentioning
confidence: 99%
“…The study was conducted in community pharmacies, distributed across the Netherlands located in both rural and urban areas, belonging to the Utrecht Pharmacy Practice network for Education and Research (UPPER) [7]. Pharmacies that provided internships for master students of the Utrecht School of Pharmacy during September 2014-February 2015 were invited to participate.…”
Section: Settingmentioning
confidence: 99%